Simultaneous presentation of malignant acanthosis nigricans and palmar fasciitis with polyarthritis syndrome in a patient of ovarian neoplasm: A rare manifestation - Jayati Dave; Sunanda Mahajan; Ankita Maheshwari; Abhishek Gupta (Indian Journal of Rheumatology, 2020)
Malignant acanthosis nigricans (MAN) is a paraneoplastic dermatosis associated most commonly with an underlying intra-abdominal malignancy. It may manifest either with or before the development of the malignancy prompt diagnosis of such paraneoplastic syndrome is often instrumental in early diagnosis of occult malignancy. Palmar fasciitis and polyarthritis syndrome is a rare disease characterized by palmar fasciitis, symmetric synovitis of the hands, fibrosis, and flexion contractures. We present a case of a 48-year-old female who presented with complaints of bilateral contracture of hands with diffuse hyperpigmentation over body folds, face, and trunk suggestive of MAN. On investigation, she was found to have ovarian carcinoma. The hand contracture was thought to be due to palmar fasciitis with polyarthritis syndrome. The patient underwent total abdominal hysterectomy with bilateral total salpingo-oophorectomy with subtle improvement in acanthosis nigricans.